Pembentukan Karakter Kristen: Implikasi Teologi Terhadap Praktik Pengajaran PAK - Yurniman Ndruru; Gina Glory Septiani Laia; Sandra R. Tapilaha (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This research investigates the relationship between the formation of Christian character and the impact of theology on the teaching of Christian Religious Education (CRE). Considering the fundamental theological principles and character education, this study aims to explore how Christian theology influences the approach to teaching CRE in shaping students' character. The research methodology involves literature review and theological analysis to explore theological concepts relevant to the formation of Christian character, as well as conducting interviews with CRE teachers to understand the application of Christian theology in their teaching practices. The findings highlight the importance of integrating Christian theological teachings, character education principles, and CRE teaching methods. The practical implications of this research emphasize the importance of developing CRE curriculum that reflects Christian values and strengthens the formation of students' Christian character within the formal education context. Thus, this research contributes to understanding the influence of Christian theology on CRE teaching practices in shaping students' Christian character.